PENGARUH MODEL PROBLEM BASED LEARNING BERBANTUAN SPEED BOARD MEDIA TERHADAP PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA KELAS V SDN 2 WERGU WETAN - Lutfi Andriyani Kutsiyah; Maela Ulfayatun Nikmah; Novita Putri Ariyani; Fitriyah Amaliyah (STKIP Subang, 2026)
Elementary school students' mathematical problem-solving ability on distance, speed, and time topics is still low because learning tends to be teacher-centered and lacks the use of interesting learning media. This study aims to determine the effect of the Problem Based Learning (PBL) model assisted by Speed ​​Board Media on improving the mathematical problem-solving ability of fifth-grade students of SDN 2 Wergu Wetan. The study used a quantitative approach with a pre-experimental type and a One Group Pretest-Posttest Design. The study population was all fifth-grade students of SDN 2 Wergu Wetan in the 2026/2027 academic year, totaling 23 students, while the research sample was 22 students determined using the total sampling technique. Data were collected through test techniques using essay questions that had been validated through content validity tests by one expert lecturer and one fifth-grade teacher. The research data were in the form of pretest and posttest scores of mathematical problem-solving ability. Data analysis was carried out using normality tests, paired sample t-tests, and N-Gain tests. The results showed that the average pretest score of 68.23 increased to 87.14 in the posttest. The results of the paired sample t-test showed a Sig. (2-tailed) value <0.001, while the average N-Gain value of 0.653 was included in the moderate category. These results indicate that the Problem Based Learning model assisted by Speed ​​Board Media has a positive and quite effective effect in improving students' mathematical problem-solving abilities. This model is recommended as an alternative for mathematics learning in elementary schools.